Case of triple extradural hematoma in a single patient: A rare case report - Jolly Sinha; Avdhesh Shukla; Vivek Kumar Kankane; Avinash Sharma; Sutradhar Sridham (Asian Journal of Medical Sciences, 2023)
Epidural hematoma (EDH) is found in 1–4% of traumatic brain injury cases. Acute triple extradural hematoma is a rare presentation of head trauma injury. In sporadic cases, they represent 0.5–1% of all extradural hematomas. Here is a case report of a 36-year-old female patient who presented to us with a head injury due to fall from a bike due to collision with a stray animal. The patient had a Glasgow Coma Scale of 9 (E2V2M5) with bilateral sluggishly reacting pupil to light. Computed tomography showed asymmetric bilateral posterior fossa EDHs along with an extradural hematoma in the right frontal region with multiple small contusions with mass effect. The surgical evacuation was performed first of the posterior fossa in the prone position and then right frontal hematoma evacuation in the supine position in the same sitting. The patient recovered well and was discharged on the 10th post-operative day with no neurological deficit. Early drainage of hematomas has been demonstrated to be an effective technique that soon decreases the intracranial pressure and promotes an efficient resolution to the neurological damage.